Social Mapping Little Fishermen Fishing Port Of Juntinyuat Village, Juntinyuat District, Indramayu District - Juenti, Nelly; Suryana, Asep Agus Handaka; Nurhayati, Atikah; Maulina, Ine (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
This research explores an in-depth understanding of the socio mapping of small-scale fishermen in Glayem Harbor, Juntinyuat Village, Juntinyuat District, Indramayu Regency. This research area was chosen due to the dominance of vessels measuring less than 10 GT which indicates the significant presence of small fishermen in Juntinyuat Village. The author's comprehensive understanding of the condition of the port in Juntinyuat Village encouraged the emergence of this research to better understand the characteristics of the social aspects of small fishermen in Juntinyuat Village and their influence on the development of small fishermen. Through this research, itis hoped that it can provide comprehensive insight into the socio dynamics of small-scale fishermen, so that it can become the basis for improving policies and more effective development efforts in the future. In achieving this goal, the method used is a survey method with the data collected in the form of descriptions. It is hoped that the results of this research can provide a positive contribution to stakeholders, local governments and related organizations in designing more sustainable policies, as well as identifying development potentials that can improve the welfare of small fishermen in Glayem Harbor, Juntinyuat Village.